2010
DOI: 10.15288/jsad.2010.71.210
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning Into and Out of Problem Drinking Across Seven Years

Abstract: ABSTRACT. Objective: The extent to which problem drinkers transition into and out of problem drinking was examined using Markov modeling. Method: Study participants (N = 1,350) were randomly sampled from one county's general population and from consecutive admissions to public and private alcohol treatment programs in the same county, and they were assessed at 1-, 3-, 5-, and 7-year follow-ups. At baseline, all met the criteria for problem drinking. Individuals were classifi ed as "problem drinkers" if they re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 59 publications
3
17
0
Order By: Relevance
“…Additionally, these findings indicate that there are substantial reductions in drinking from baseline among individuals that we have traditionally labeled as treatment non-responders, based on the no heavy drinking responder definition. The notion that individuals can move in and out of heavy drinking and be functioning quite well is consistent with epidemiological data (Dawson et al, 2007; Delucchi and Weisner, 2010) and recent studies in AUD samples (Wilson et al, 2016; Witkiewitz et al, 2017). On average, the majority of patients (those in Class 1) show considerable improvements in the frequency and quantity of alcohol consumed during and after treatment, despite being categorized as non-responders by virtue of having had at least one heavy drinking day in a specific period during the clinical trial.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Additionally, these findings indicate that there are substantial reductions in drinking from baseline among individuals that we have traditionally labeled as treatment non-responders, based on the no heavy drinking responder definition. The notion that individuals can move in and out of heavy drinking and be functioning quite well is consistent with epidemiological data (Dawson et al, 2007; Delucchi and Weisner, 2010) and recent studies in AUD samples (Wilson et al, 2016; Witkiewitz et al, 2017). On average, the majority of patients (those in Class 1) show considerable improvements in the frequency and quantity of alcohol consumed during and after treatment, despite being categorized as non-responders by virtue of having had at least one heavy drinking day in a specific period during the clinical trial.…”
Section: Discussionsupporting
confidence: 87%
“…The present study can be viewed as providing a high-definition view of the temporal stability of drinking behavior from month-to-month during treatment, which has previously been assessed in different epidemiological and clinical samples over seven years (Delucchi and Weisner, 2010) and three years (Dawson et al, 2007). Consistent with these prior findings, our analyses showed increasing stability in drinking patterns, but are the first to highlight the relative stability of drinking behavior across four months of treatment, which has important research and clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…But if that were the case, we should be seeing cycling up and down, which we do not. Additionally, as we have shown in other work, overall problem drinking is fairly steady, but one is more likely to stop problem drinking than to relapse (Delucchi and Weisner, 2010). Finally, it may be that, when we recontacted them, they felt pressured to say they were drinking less because somehow they were embarrassed to admit doing so.…”
Section: Discussionmentioning
confidence: 73%
“…Note that, for both Models 1 and 2, respondents can move in and out of problem drinking status over the follow-up periods, and therefore problem drinkers and non-problem drinkers refer not to a fi xed set of respondents but to a changing set who are problem (or not problem) drinkers at the various follow-up waves. However, Delucchi and Weisner (2010) provide evidence of relative stability over time. The longitudinal models estimated provide, in a sense, an averaged relationship over time, while simultaneously accounting for within-individual correlation in error of prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Examining volume consumed in the past 12 months, Delucchi et al (2004) found fi ve distinct drinking trajectories, described as early nondrinkers (reports of very low or no consumption across the four interviews, 8% of the sample), quitters (drinking 12 months prior to baseline but very low or no consumption afterward, 7%), gradual improvers (gradually decreasing volume over time, 12%), moderate drinkers (fairly constant and moderate consumption over time, 21%), and heavy drinkers (constant and higher consumption over time, 52%). Trajectories of problem drinking were explored in Delucchi and Weisner (2010), where fi ve trajectories were again found and were described as non-problem drinkers over time (42% of the sample), late problem drinkers (2%), early remitters (13%), later remitters (5%), and consistent problem drinkers (38%). Here in this study, an alternative method was used to capture heterogeneity in drinking behaviors found from previous analyses: namely, conditioning on the respondent's prior problem drinking state and examining the role of contact with medical settings in assessing the likelihood of problem drinking at the subsequent follow-up.…”
mentioning
confidence: 99%